The Code Breaker Jennifer Doudna, Gene Editing and the future of human race - Isaacson, Walter (New York Simon and Schuster, 2021)
In 2012, Nobel Prize winning scientist Jennifer Doudna hit upon an invention that will transform the future of the human race: an easy-to-use tool that can edit DNA.
Keywords: Human Race